Aggregate transport and utilization: ecological footprint and environmental impacts - Agioutantis, Z.; Komnitsas, K.; Athousaki, A. (Bulletin of the Geological Society of Greece, 2013)
The Ecological Footprint (EF) measures how much of the biosphere’s annual regenerative capacity is required to renew the natural resources used by a defined population in a given year. In essence, the EF is a resource accounting tool that measures how much biologically productive land and sea is used by a given population or activity, and compares this with the available land and sea. Productive land and sea support population demands for food, fiber, timber, energy, and space for infrastructure. These areas also absorb gaseous emissions (i.e. CO2) generated from human activities. The present paper discusses a methodology that allows the parametric estimation of the EF due to the transport of aggregates to urban areas as a function of tonnage and distance.